THE EFFECTIVENESS OF TED TALKS TOWARDS STUDENTS’ PROFICIENCY LEVEL - Azureen Abd Aziz; Suhaila Ngadiron, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Proficiency has become a crucial aspect of learning English language. The aim of this study is to find out the effectiveness of using English videos from TED talks towards students’ proficiency level. This study employed a quantitative research design. To fulfil this purpose, 50 diploma students were selected from a private university in Negeri Sembilan. These participants were then divided into two equal groups of experimental and control. A graded presentation was administered as a pre-test for both groups prior to the treatment. There were three sessions of presentations conducted with both groups in which the experimental group watched the TED talks and the control group underwent the traditional teaching method. After the sessions, post-test were given to both groups. The scores of both tests were collected and analyzed using descriptive statistics. Results revealed that the experimental group experienced improvement in their speaking compared to the control group. Few recommendations are presented based on the research findings.